Comprehensive characterization of a novel UWB elliptical planar monopole antenna - Marindra, Adi Mahmud Jaya; Promwong, Sathaporn; Takada, Jun Ichi (My University, 2012)
The rise of research in ultra wideband (UWB) antenna design must be followed by a proper method of antenna characterization. The emerging concept of UWB impulse radio (UWB-IR) compels the performance evaluation of UWB antenna should be assessed in different ways from narrowband antennas. In this paper, a comprehensive characterization of UWB antenna will be discussed. Based on the theory of antenna transfer function in frequency domain, some UWB transmission parameters in time domain are derived, i.e. waveform correlation, waveform width stretch ratio, and waveform relative gain. For practical testing, we propose a novel UWB elliptical planar monopole antenna as the characterized antenna. The results show that the overall performance and characteristic of the proposed antenna is very good, especially at the antenna boresight. The derived parameters can quantitatively characterize the UWB antenna for all the measured directions so that the detail of transmission performance of the UWB antenna could be known. Hopefully, the characterization scheme with the proposed antenna presented in this paper provide useful insight either for UWB antenna design or for evaluating UWB antenna performance. © 2012 IEEE.
Keywords: characterization; performance; ultra wideband (UWB); UWB elliptical planar monopole antenna